Henipavirus sero-surveillance in horses and pigs from Northern Nigeria - Adamu, Andrew Musa; McNabb, Leanne; Adikwu, Alex Adikwu; Jibril, Yakubu Jibril; Idoko, Sunday Idoko; Turaki, Aliyu Usman; Abalaka, Samson Eneojo; Edeh, Richard Emmanuel; Egwu, Godwin Onyemaechi; Adah, Mohammed Ignatius; Halpin, Kim (Frontiers in Virology, 2022)
Hendra virus and Nipah virus are considered emerging viruses and are the cause of severe zoonotic disease which occurs in humans who have had close contact with horses and pigs in Australia and Asia respectively. Both viruses belong to the genus Henipavirus. Although there are large populations of horses and pigs in northern Nigeria, no previous studies in this region have investigated Henipavirus sero-surveillance in horses and pigs using the gold standard test, the serum neutralization test (SNT). A total of 536 apparently healthy horses and 508 apparently healthy pigs were sampled within northern Nigeria in 2018. Serum samples were tested using either the Henipavirus virus Luminex binding assays for horses or the Hendra virus Competitive ELISA and Nipah virus Indirect ELISA for pigs as initial screening tests followed by the confirmatory Hendra and Nipah virus SNT for both species, according to accredited protocols at the Australian Centre for Disease Preparedness. Although some horse and pig samples cross-reacted or reacted weakly in the screening test, confirmatory SNT for all of them proved negative. The present study reveals the absence of Hendra and Nipah antibodies in horses and pigs in northern Nigeria, which is consistent with the absence of observable disease in the field. However, the continuous inter and intra trans-boundary animal movement and trade in Nigeria calls for the continuous evaluation of henipavirus status of susceptible animals to safeguard both animal and human health.